2022
DOI: 10.3390/ijerph19063650
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Temporal and Spatial Dynamics of Regional Water Resources Security in the DPSIR Framework in Jiangxi Province, China

Abstract: Water resources are critical for the survival and prosperity of both natural and socioeconomic systems. A good and informational water resources evaluation system is substantial in monitoring and maintaining sustainable use of water. The Driver-Pressure-State-Impact-Response (DPSIR) framework is a widely used general framework that enabled the measurement of water resources security in five different environmental and socioeconomic subsystems: driver, pressure, state, impact, and response. Methodologically, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…It systematically and comprehensively considers the relationship between humans and the environment, and can reflect the interaction between tourism activities and the ecological environment and their impacts, thus providing feedback to human activities on behalf of humans. The model has been widely used in sustainable development evaluation [ 32 , 33 ], eco-security evaluation [ 34 , 35 ], and ecological vulnerability [ 19 , 36 ] and water security evaluation [ 37 , 38 ]. In this study, the DPSIR model was used to construct the tourism eco-security index system of the Yellow River basin.…”
Section: Methodsmentioning
confidence: 99%
“…It systematically and comprehensively considers the relationship between humans and the environment, and can reflect the interaction between tourism activities and the ecological environment and their impacts, thus providing feedback to human activities on behalf of humans. The model has been widely used in sustainable development evaluation [ 32 , 33 ], eco-security evaluation [ 34 , 35 ], and ecological vulnerability [ 19 , 36 ] and water security evaluation [ 37 , 38 ]. In this study, the DPSIR model was used to construct the tourism eco-security index system of the Yellow River basin.…”
Section: Methodsmentioning
confidence: 99%
“…The DP-SIR model of the watershed ecosystem security system is an orderly and sustainable operation and complex open-loop system emphasizing the symbiotic relationship between human activities and ecosystems (Kharrazi et al, 2017;Zhao et al, 2021b). Under the principle of circular cumulative causality, the development of human activities serves as a 'driving' (D) subsystem that affects the ecological security of the watershed (Lu et al, 2022). The development of this subsystem will increase the demand on the basin resources and environment.…”
Section: Evaluation Index Based On the Dpsir Modelmentioning
confidence: 99%
“…It identifies the cause-effect relationships in five economic and social development categories: driving forces (D) that exert pressure (P) on the environment; changes in the state of the environment (S) and impacts (I) on the ecosystem, human health, and other materials; and society's preventive, adaptive, or curative solution responses (R) to the driving forces, pressures, states, or impacts (Jago-on et al, 2009). DPSIR has been wildly used for analysing environmental problems emanating from human activities in policy-making and research (Gari et al, 2018;Lu et al, 2022;Agramont et al, 2022), including water issues (Kagalou et al, 2012;Hashemi et al, 2014;Gari et al, 2018;Ashfaq et al, 2018;Lu et al, 2022). Hashemi et al (2014) found the framework useful for analysing the changing state of floods, structuring data, and examining leverage points at which appropriate responses can be exerted.…”
Section: Introductionmentioning
confidence: 99%